CHARACTER AND VALUE BUILDING THROUGH PROVISION OF QUALITY EDUCATION IN ONDO STATE SECONDARY SCHOOL - Akingunloye, Babatunde Akinwande; Agbara, Clement Olugbenro; Akinbayo, Temitope oluwafemi AKINBAYO; Opadokun, Olufunke Adeitan (Spektra: Jurnal Ilmu-ilmu Sosial, 2025)
This study evaluated student characters in schools, analysed the role of school staff in shaping good characters, explored parental influence on student character, and examined measures guiding schools in character development. It used a descriptive survey design with a sample of 540 students from public secondary schools in Ondo State. Results revealed that students arrive early (mean: 3.71, SD: 1.12) and attend classes regularly (mean: 3.80, SD: 1.03). Collaboration and helping behavior (means: 3.47 and 3.53, SDs: 1.16 and 1.13), as are honesty (mean: 3.71, SD: 1.12), respect for authority (mean: 3.87, SD: 0.93). Resilience (mean: 3.41, SD: 1.08), adherence to school hours (mean: 3.24, SD: 1.24). Teachers exhibit punctuality (mean: 3.87, SD: 0.93), confidence (mean: 3.67, SD: 1.07), and approachability (mean: 3.59, SD: 1.04). Parental support (mean: 3.62, SD: 1.07) and school regulatory measures (mean: 3.67, SD: 1.07). The findings showed the importance of cohesive efforts by students, staff, and parents in fostering positive character traits and values in school settings. The study concluded students’ value and character can be shaped through quality education.